An evaluation of role of the informational components in decision-making process of health systems’ managers based on World Health Organization’s standards - Mirzaeian, Razieh; Habibi, Mahboobeh; Shirvani, Mina; Sharifi-Rad, Javad (International Journal of Research in Medical Sciences, 2017)
Background:Objective of current study was to enhance the effectiveness of the organization its goals, health system managers must possess sufficient knowledge about health information systems which are regarded as the basis of decision-making at different managerial levels. The present research tried to explore the extent of meeting the information management components and evaluate its role in decision-making of health systems' managers. Methods:Descriptive-analytical in nature, this study intended to examine the urban and rural health centers as well as health system. Data were collected through a self-designed checklist produced based on the World Health Organization’s standards which include the information presentation (6 components), information interpretation (5 components) and using information in decision-making process (1 component) for urban and rural health centers. The checklist designed for health system included needs-analysis and information collection, presentation, processing and interpretation components. The gathered data were then put into SPSS version of 13 and analyzed using independent t-test. Results:The findings of the study revealed that compared to urban centers, the rural health centers had a higher level in meeting the components in 3 main areas i.e. information presentation, information interpretation and information use in decision-making process (P <0.05). As far as sub-measures were concerned, the rural health centers gained a higher mean score for data presentation in the health system and other interpretation-related components (P <0.05). The level of meeting data presentation components revealed that the mean score for using data for decision-making purposes was high while the mean score for data processing was found to be low. Conclusion: Proper processing and appropriate use of data in the decision-making by the managers and public policy-makers are the missing requirements which must be taken into account.